Comparison of Learning Areas Between Offline and Online Learning in the Office Administration Education Study Program, UNM - Muhammad Darwis; Muh. Husain; Jamaluddin Jamaluddin; Ahmad Syaekhu (Pinisi Journal of Education and Management, 2022)
Comparison of the realm of learning between offline and online learning in the Office Administration Education Study Program, Universitas Negeri Makassar. This study aims to compare the realm of learning between offline and online learning in the Office Administration Education Study Program FIS-H UNM. To determine the purpose of the study, an ex post facto quantitative research approach was used with a comparative level of explanation. Respondents in this study amounted to 93 people using data collection techniques through observation, questionnaires, and documentation. The data obtained from the research results were then processed using data analysis techniques consisting of descriptive statistical analysis and inferential statistical analysis. The results showed that offline learning was in the very good category while online learning was in a good category. For the results of student academic achievement during offline learning, academic achievement or semester achievement index (IPS) is higher than academic achievement or semester achievement index (IPS) during online learning at the Office Administration Education Study Program, Universitas Negeri Makassar. Based on the analysis of variance (ANAVA) and t-test conducted, it was stated that there was no significant difference in student academic achievement between offline and online learning in the Office Administration Education Study Program, Universitas Negeri Makassar.